The Islamic Reform Movement and the Renewal of the Inheritance System in Minangkabau - Fahrul Razi; Lalu Muhammad Nurul Wathoni; Ihsan Azhari; Nadia Rezky; Muhammad Maghfurrohman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The acculturation of customs and Islam in Minangkabau did not emerge spontaneously, but rather resulted from a long debate between the Islamic reformist group and the traditionalist adat group.This research aims to examine the long history of debates between the reformist Padri movement and the traditionalist adat group, as well as between the Mudo and Tuo movements in the 19th and 20th centuries, and how these debates are related to the reform of inheritance laws in Minangkabau.The research method used in this study is the library method, which involves collecting, reading, and reviewing books and journals related to the discussion of this research using a historical approach.The results of this study found the historical debate between the reformist Padri faction and the traditionalist adat faction.The Padri and adat factions can unite to stop conflicts among brothers and reaffirm the agreement regarding the relationship between Minangkabau customs and Islamic law.In terms of inheritance, then the livelihood can be divided based on Islamic inheritance law.The Mudo movement questioned the act of bid'ah, initiated reforms in religious thought, and modernized the education, social, and political systems.In inheritance law, the opinion of Sheikh Abdullah Karim Amrullah as a young figure who distinguished between Islamic inheritance and customary inheritance was accepted by various circles.The Padri movement and the Young Minangkabau movement initially failed to achieve social integration within the Minangkabau community and caused division, but the policies of Tuanku Imam Bonjol and Syekh Abdullah Karim Amrullah later succeeded in achieving social integration within the Minangkabau community through the adaptation of customs and the alignment of goals, maintained through agreements and consensus on customs.